MENINGKATKAN KEPUASAN PELANGGAN MELALUI PERAN MEDIASI KEPUTUSAN PEMBELIAN DI AYAM BAKAR KALASAN WONG YOGYA, CIANGSANA - Dinda Putri Mardatilah; Parlagutan Silitonga (Human Capital Development, 2022)
This study aims to analyze the effect of quality of product and price perception on customer satisfaction through purchase decision at Ayam Bakar Kalasan Wong Yogya, Ciangsana. Using primary data obtained from 132 respondents at Ayam Bakar Kalasan Wong Yogya, Ciangsana. The data analysis methods used in this study are validity tests and reliability tests. While hypothesis testing includes path analysis, evaluation of measurement models and structural models, direct influences, and indirect influences. The author uses quantitative descriptive methode, namely by analyzing data using SmartPLS 3.0. This study shows that product quality and price perception have a positive and significant impact on purchasing decision. Meanwhile, product quality and price perception have a positive and significant effect on customer satisfaction and purchase decisions have a significant effect on customer satisfaction. Keywords : Customer Satisfaction; Price Perception; Purchase Decision; Quality Product